Fundamentals of Citrus Canker Management - Lavern W. Timmer; James H. Graham; Holly L. Chamberlain (EDIS)
PP-231, a 5-page fact sheet by L. W. Timmer, J. H. Graham and H. L. Chamberlain, provides fundamentals of citrus canker management now that the program to eradicate affected trees has ended. It includes information about protecting canker-free areas through decontamination and inoculum suppression, and for areas where canker is endemic it describes the use of windbreaks, copper sprays, leafminer control, and canker-resistant varieties. Published by the UF Department of Plant Pathology, July 2006.